Agrobacterium-mediated genetic transformation of two varieties of Brassica: optimization of protocol - Khan, MMA; Robin, ABMAHK; Nazim-Ud-Dowla, MAN; Talukder, SK; Hassan, L (Bangladesh Journal of Agricultural Research, 2010)
Two rapeseed varieties, namely Tori-7 and BARI Sarisha-8, respectively, from Brassica rapa and Brassica napus were selected to observe the transformation ability. Petioles were inoculated in Agrobacterium tumefaciens strain LBA 4404 carrying a binary vector pBl2l with GUS (reporter) and nptII (kanamycin resistant) gene. The transformation experiment was performed by optimizing two important factors: preculture time and co-cultivation time and also selected out the best variety. Infection was most effective when explants were pre-cultured for 72 hours (80% GUS positive). and co-cultivated for 72 hours (72% GUS positive). The variety Tori-7 showed the best response to GUS assay (65% GUS positive). Callus induction was the highest in Tori-7, which were 6% with 72 hours of preculture period and 9% in 48 hours of co-cultivation. Number of putative transformed plantlets were highest in Tori-7 (7 plants) followed by BARI Sarisha-8 (3 plants). Key words: Transformation; Brassica; GUS; Agrobacterium. DOI: 10.3329/bjar.v34i2.5802 Bangladesh J. Agril. Res. 34(2): 287-301, June 2009